Literasi Media pada Generasi Z di Era Digital - Hasibuan, Mutiara Sany; Lubis, Malan; Surip, M. (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the media literacy of generation Z in the digital era among pupils and students at SMK Negeri 7 Medan class XI MPLB 1 through a questionnaire and distributed using Google Form.  The results of this research reveal that the majority of Generation Z (82.1%) said they like literacy and 92.9% of Generation Z said that using social media for literacy has positive and negative influences, and some of them spent less than 1 hour on it. literacy in social media.